Chronic kidney disease in outpatients with arterial hypertension: clinical characteristics and treatment efficacy (according to the national registry) - Elena V. Oschepkova; Anna V. Aksenova; Alexey А. Orlovsky; Irina E. Chazova (Терапевтический архив, 2022)
Аim. To investigate the clinical characteristics and quality of treatment (according to the national guidelines) of patients with arterial hypertension (AH) and chronic kidney disease observed in primary health care.